2012
DOI: 10.1111/j.1741-3729.2011.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Community and School Mental Health Services by Custodial Grandchildren

Abstract: We examined patterns and predictors of the perceived need, use, and unmet need for mental health services by custodial grandchildren within both the school-based and community-based delivery sectors. Data were self-reported by a national sample of 610 custodial grandmothers providing full-time care to grandchildren ages 6 to 17 in the absence of biological parents. Although overlapping use of services across both sectors was common, the overall use of school-based services (51%) was higher than that of communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…However, few studies have examined the stress-buffering effect of volunteering on psychological distress among grandparent caregivers. It is critically important to understand whether and how volunteer engagement helps mitigate psychological distress, because grandparent caregivers’ increased psychological distress is associated with poor parenting and family functioning, negative parent–child interaction, and grandchildren’s academic underachievement and behavioral problems (Kelley et al., 2000; Montoro-Rodríguez, Smith, & Palmieri, 2012). Furthermore, increased psychological distress of grandparent caregivers may reduce their physical and cognitive function and exacerbate health problems (Fuller-Thomson & Minkler, 2000; Waldrop & Weber, 2001).…”
Section: Effects Of Volunteering On Stressorsmentioning
confidence: 99%
“…However, few studies have examined the stress-buffering effect of volunteering on psychological distress among grandparent caregivers. It is critically important to understand whether and how volunteer engagement helps mitigate psychological distress, because grandparent caregivers’ increased psychological distress is associated with poor parenting and family functioning, negative parent–child interaction, and grandchildren’s academic underachievement and behavioral problems (Kelley et al., 2000; Montoro-Rodríguez, Smith, & Palmieri, 2012). Furthermore, increased psychological distress of grandparent caregivers may reduce their physical and cognitive function and exacerbate health problems (Fuller-Thomson & Minkler, 2000; Waldrop & Weber, 2001).…”
Section: Effects Of Volunteering On Stressorsmentioning
confidence: 99%
“…computer support, legal support, support groups, financial assistance services, mental health services) for their grandchildren in their care (Fernandes et al, 2021 ; Letiecq et al, 2008 ; Montoro‐Rodríguez et al, 2012 ; Yancura, 2013 ), impacting the well‐being of grandchildren. For example, studies have indicated that grandparents' legal rights challenges, fear of the child welfare system and unawareness of relevant policies and resources significantly limited their access to financial assistance, mental health services, parenting services, afterschool programmes and other services for grandchildren in care (Fernandes et al, 2021 ; Letiecq et al, 2008 ; Montoro‐Rodríguez et al, 2012 ; Van Etten & Gautam, 2012 ). Lack of access to these services may reduce custodial grandchildren's quality of life, creating the potential for a greater risk of poor outcomes in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Variations of this model have informed numerous health service utilization studies since the 1960s, including several on custodial grandfamilies per se (Montoro-Rodriguez, Smith, & Palmieri, 2012; G. C. Smith, Montoro-Rodriguez, & Palmieri, 2010; Yancura, 2013). According to Andersen, service use is affected by three broad characteristics: (a) predisposing factors that directly influence use (e.g., as age and gender), (b) enabling resources that assist or impede use (e.g., income and social support), (c) and need variables (e.g., clinical symptoms).…”
mentioning
confidence: 99%
“…These questions are considered from the perspective of Andersen's (2008) behavioral model of health services use. Variations of this model have informed numerous health service utilization studies since the 1960s, including several on custodial grandfamilies per se (Montoro-Rodriguez, Smith, & Palmieri, 2012;G. C. Smith, Montoro-Rodriguez, & Palmieri, 2010;Yancura, 2013).…”
mentioning
confidence: 99%